Pengaruh Ketinggian Tanaman Terhadap Keberhasilan Fogging dalam Mengendalikan Ulat Api (Setothosea Asigna) di PT Socfindo Kebun Matapao - Abdul Munir; Edi Wiraguna (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
One of the common pests found in oil palm is the nettle caterpillar (Setothosea asigna), which can consume between 300 to 500 cm² of leaves per individual. A single oil palm tree may host between 5 to 10 of these caterpillars. This study aimed to evaluate the effectiveness of fogging in controlling Setothosea asigna infestations on oil palm trees of varying heights at PT Socfindo, Matapao Estate, North Sumatra. The research was conducted in two plantation blocks with different tree heights: block 49 with trees ranging from 9–12 meters and block 46 with trees ranging from 3–6 meters. Data collection involved an initial census to count caterpillars before fogging, followed by a post-fogging census to observe mortality rates. Data were analyzed using a t-test to compare the effectiveness of fogging between tall and short trees. The results showed that fogging was more effective on shorter trees, with an average mortality rate of 94%, compared to 90% on taller trees.